Pengaruh Iklim Kerja dan Kemampuan Kerja Terhadap Motivasi dan Kinerja Aparatur pada Bagian Umum Sekretariat DPRD Provinsi Sulawesi Tenggara - Ismail Pagala; Abd. Azis Muthalib; Fauzih (SIGMA: Journal of Economic and Business, 2018)
This study aims to identify and analyze: 1) The effect of work climate on work motivation of personnel, 2) Effect of work ability on work motivation of personnel, 3) Effect of work environment on the performance of the apparatus 4) The effect of the ability to work on the performance of the apparatus, 5) The effect of work motivation on performance of the apparatus. 6) Work motivation in mediating the effects of work climate on the performance of the apparatus and 7) Motivation in mediating the effects of work on the performance capability of the apparatus to the Parliament Secretariat General Section of Southeast Sulawesi province.The population of this study was 37 personnel on Parliament Secretariat General Section of Southeast Sulawesi province were selected by census / total sampling. The technique of collecting data using questionnaires and document research. Data analysis technique used is descriptive statistical analysis and analysis of Partial Least Square (PLS).The results of this study concluded that: 1) The climate of positive effect but not significant to the work motivation of personnel 2) The ability to work significant positive effect on work motivation of personnel 3) The climate of significant positive effect on the performance of the apparatus 4) Ability to work significant positive effect on the performance of the apparatus 5) work motivation is positive but not significant effect on the performance of the apparatus 6) Motivation does not mediate the effect of climate on the job performance of the apparatus and 7) Motivation does not mediate the effect of the ability to work on the performance of the apparatus at the parliament Secretariat General Section of Southeast Sulawesi province.